Current Epidemiology of Serogroup W Meningococcal Disease—United States, 2010–2015. (4th October 2017) - Soeters, Heidi; Blain, Amy; Chang, How-Yi; Whaley, Melissa; Macneil, Jessica
Abstract: Background: Serogroup W (NmW) meningococcal disease is a rare but severe infection. Following an NmW outbreak after the Hajj in 2000, NmW disease, predominantly caused by sequence type (ST)-11 clonal complex (cc), rapidly increased in South Africa, South America, and the UK. We describe NmW meningococcal disease epidemiology in the USA during 2010–2015. Methods: Data were collected from the National Notifiable Diseases Surveillance System, Active Bacterial Core surveillance, and state health departments. Isolates were serogrouped via slide agglutination and real-time polymerase chain reaction. For cases lacking a serogroup result at CDC, the state result was used. Case-fatality ratios (CFR) were calculated using the proportion of cases with known outcomes as the denominator. cc and ST were determined using multilocus sequence typing (MLST). Results: From 2010 to 2015, 3, 504 meningococcal disease cases were reported to CDC; 2, 976 (85%) had a serogroup result, of which 290 (10%) were NmW. Although the number of NmW cases reported annually remained fairly stable (range: 40– 57), the total number of reported meningococcal disease cases decreased by 60%, and the proportion of cases due to NmW increased from 6% (42/830) in 2010 to 12% (40/332) in 2015. The majority of NmW cases were reported from five states: Florida ( n = 106), California ( n = 31), New York ( n = 25), Georgia ( n = 19), and Oregon ( n = 11). Half of people with NmW disease were male, 185 (64%) were white, and 84 (29%) were Hispanic. The median age was 51 years (interquartile range: 26– 70). Overall, 20% (52/259) of NmW cases were fatal, compared with CFRs for serogroups B (15%), Y (18%), or C (24%). NmW CFR was highest among adults aged 50–59 years (38%). MLST results were available for 119 (41%) of NmW cases: 76 (64%) were cc11, 40 (34%) were cc22, and 1 each were cc23, cc32, and an unassigned cc. cc appeared to be geographically associated: cc11 was concentrated in Florida and Georgia, while cc22 predominated on the West coast. Within cc11, the majority of isolates (86%) were ST-11, and within cc22 the majority (73%) were ST-22. Conclusion: A rapid increase in NmW disease has not been observed in the USA. Most NmW cases were reported in a limited number of states, with geographic differences in clonal complex. Disclosures: All authors: No reported disclosures.